ESTUDIOS DE TAXONOMIA MOLECULAR EN POBLACIONES DE TRIATOMA INFESTANS (KLUG, 1934) Y TRIATOMA SPINOLAI PORTER, 1933 (HEMIPTERA: TRIATOMINAE) - Frías L., Daniel; Kattan, Francisca (Acta Entomológica Chilena, 2022)
The enzymalic movililv differences belween Trialuma infestan* and T. spmnlat are described in ihis paper. Funhermore, the differences in genetic frequencies in bolh species are also discussed. For each species ihe idenlity and genelic distance coefficient is calculated. T he taxonomic status of these populations is too discussed.